Quran liberation and pluralism : an islamic perspective of interreligious solidarity against oppression - "Esack, Farid" (Oxford, 2006)
The demise of apartheid in South Africa in the 1980s followed an unprecedented unity in struggle against oppression from members of different faith traditions. This work details how South African Muslims were brought into conflict with the Qu'ran, which denied virtue outside Islam, and so did not allow them to co-operate with other oppressed groups. It reflects on passages from the Qu'ran and provides interpretations which support solidarity for change, combining social history, politics and theology.
Keywords: Islam